Using [1‐13C]lactic acid for hyperpolarized 13C MR cardiac studies. Issue 6 (9th July 2014) - Chen, Albert P.; Lau, Justin Y.C.; Alvares, Rohan D.A.; Cunningham, Charles H.
<x xml:space="preserve">Abstract</x> Purpose Hyperpolarized [1‐13C]lactate in solution may be a clinically relevant and safe substrate for real time MR investigations of key metabolic pathways. The potential of using hyperpolarized [1‐13C]lactate for magnetic resonance studies of cardiac metabolism in vivo was explored. Methods Neat [1‐13C]lactic acid was hyperpolarized using the dynamic nuclear polarization process. Cardiac MR spectroscopy experiments were performed in vivo using hyperpolarized [1‐13C]lactate and [1‐13C]pyruvate in solutions. Results A high degree of polarization was achieved for [1‐13C]lactate in solution (16.7%). 13C‐bicarbonate was observed in rat hearts in vivo after either hyperpolarized [1‐13C]lactate or hyperpolarized [1‐13C]pyruvate was infused, but lower 13C‐bicarbonate to substrate ratio was observed with hyperpolarized [1‐13C]lactate infusions. The response of 13C‐bicarbonate signal as a function of hyperpolarized [1‐13C]lactate doses was also investigated and a saturation of 13C‐bicarbonate signal was observed at the highest dose of [1‐13C]lactate used (0.69 mmol/kg). Conclusion This study demonstrated that the use of neat [1‐13C]lactic acid as the DNP sample is a potential alternative to [1‐13C]pyruvic acid for cardiac hyperpolarized 13C MR studies. Hyperpolarized [1‐13C]lactate may enable noninvasive assessment of cardiac PDH flux in cardiac patients in the near future. Magn Reson Med, 2014. © 2014 Wiley Periodicals, Inc. Magn Reson Med 73:2087–2093, 2015. © 2014 Wiley Periodicals, Inc.